Fate mapping of hematopoietic stem cells reveals two pathways of native thrombopoiesis - Morcos, Mina; Li, Congxin; Munz, Clara M.; Greco, Alessandro; Dressel, Nicole; Reinhardt, Susanne; Sameith, Katrin; Dahl, Andreas; Becker, Nils B.; Roers, Axel; Höfer, Thomas; Gerbaulet, Alexander (Nature Communications, 2022)
Hematopoietic stem cells (HSCs) produce highly diverse cell lineages. Here, we chart native lineage pathways emanating from HSCs and define their physiological regulation by computationally integrating experimental approaches for fate mapping, mitotic tracking, and single-cell RNA sequencing. We find that lineages begin to split when cells leave the tip HSC population, marked by high Sca-1 and CD201 expression. Downstream, HSCs either retain high Sca-1 expression and the ability to generate lymphocytes, or irreversibly reduce Sca-1 level and enter into erythro-myelopoiesis or thrombopoiesis. Thrombopoiesis is the sum of two pathways that make comparable contributions in steady state, a long route via multipotent progenitors and CD48hi megakaryocyte progenitors (MkPs), and a short route from HSCs to developmentally distinct CD48−/lo MkPs. Enhanced thrombopoietin signaling differentially accelerates the short pathway, enabling a rapid response to increasing demand. In sum, we provide a blueprint for mapping physiological differentiation fluxes from HSCs and decipher two functionally distinct pathways of native thrombopoiesis.
Gesehen am 28.08.2022